Intercultural citizenship education in an EFL (English as a Foreign Language) online project in Argentina - Porto, Melina (2014)
In this article, I describe an online intercultural citizenship experience in an EFL classroom in Argentina. An action research project on the Malvinas/Falklands war fought between Argentina and the UK in 1982 was carried out in 2012. Through a comparative methodology involving Argentine and English foreign language classes, students develop a critical perspective on texts while they also create an international identification, different from their national/regional identifications. While the existing body of work on intercultural citizenship and criticality in the foreign language classroom is abundant in Europe, North America and Asia, empirical studies hardly exist in this region and one of the questions to be answered deals with the transferability of curriculum research across continents. After a description of the theoretical framework and the project itself, I present student samples and analysis that provide evidence that this intercultural citizenship project was fruitfully implemented for the first time in Argentinean Higher Education in the foreign language classroom. I then outline the significance of the project from the point of view of online intercultural communication and the theory of intercultural citizenship.